How to Approach Submucosal Lesions in the Gastrointestinal Tract: Different Ideas between China and USA - Rui Ping Gao; Yue Ping Zhang; Qiu Mei Li (Gastroenterology Research and Practice)
Between 2019 and 2020, the author Gao pursued advanced endoscopic training at the University of Mississippi Medical Center in the USA. She experienced certain different ideas between the East (China) and the West (USA) in terms of endoscopic approach to the submucosal tumors (SMTs) or lesions in the gastrointestinal (GI) tract. In the West (USA), when SMTs are found on gastroscopy, the main goal of endoscopists is to obtain a tissue diagnosis through endoscopic ultrasound-guided fine-needle aspiration or biopsy (EUS-FNA or FNB) or single incision needle-knife biopsy (SINK); if immunohistochemical tests confirmed the GISTs, the first-line treatment is local surgery, that is, diagnosis before treatment, whereas in China, SMTs will be completely resected with endoscopic technology for those with no lymph node metastasis or extremely low risk of lymph node metastasis. There may not be pathological tissue at first, that is, treatment before diagnosis.